OBJEK SEWA YANG DISEWA ULANG PEMILIK DI KELURAHAN SIHITANG KECAMATAN PADANGSIDIMPUAN TENGGARA KOTA PADANGSIDIMPUAN (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2017)
One form of muamalah that is often practiced in the community is renting or Ijarah. The essence of leasing is to sell benefits, namely the transfer of use rights (benefits) to an item and service for a certain period of time through the payment of rent / wages without being followed by the transfer of ownership of goods. The problem in this study is how the rent-leasing practice in Sihitang Sub-District, Southeast Padangsidimpuan Subdistrict, Padangsidimpuan City and how Islamic law views the object of rent that the owner leases in Sihitang Sub-District, Southeast Padangsidimpuan Subdistrict, Padangsidimpuan City. The purpose of this study is to know the practice of renting in Sihitang Sub-District, Southeast Padangsidimpuan Subdistrict, Padangsidimpuan City and to know the views of Islamic law on the object of rent which the owner leases in Sihitang Sub-District, Southeast Padangsidimpuan Subdistrict, Padangsidimpuan City.The conclusion in this study is the practice of leasing which is done by the community of Sihitang Lingkungan 1 and 2 villages that there is an object that has been leased by the owner to be rented to another person (second tenant) because of economic needs. Furthermore, the practice of renting with leasing objects that are rented by the owner by the community of Sihitang Lingkungan 1 and 2 is not in line with Islamic teachings. Because it seems detrimental to the tenant because he feels uncomfortable with the repetition of rents made by the owner of the boarding room, and the benefits of goods leased in the lease agreement must be enjoyed by the tenant, which is a commodity purchased with rent. In addition, these actions cause other people's rights takers without their permission and do not get compensation. Leases that are recommended in Islam must have the principle of fairness, honesty and truth, and mutual benefit.